Assessment of biochar and/or nano zero-valent iron for the stabilisation of Zn, Pb and Cd: A temporal study of solid phase geochemistry under changing soil conditions - Mitzia, Aikaterini; Vítková, Martina; Komárek, Michael (Chemosphere, 2020)
The remediation of a soil contaminated with Zn, Pb and Cd was tested by using biochar (BC), nano zero-valent iron (nZVI) and a combination of these two (BC + nZVI). Each amendment was individually applied to the soil at 2 wt%. We tested the influence of (i) the used amendments, (ii) time, and (iii) soil moisture conditions on the metal availability and soil physico-chemical parameters using various extraction methods, as well as soil pore water samplings. We found that metal availability was mainly affected by pH under the influence of time and water content. Among the tested treatments, BC was the most successful, resulting in the lowest amounts of the target metals in the pore water and the smallest temporal changes in metal concentrations and pH in the soil. The use of nZVI efficiently decreased water-extractable Pb in the short- and long-term. The BC + nZVI treatment also yielded promising results regarding the immobilisation of the studied metals. Time provoked a general decrease in pH, which occasionally increased the available metal concentrations. Raising the soil water content increased the pH and subsequently lowered the available metal concentrations in the pore water. The mechanisms of metal stabilisation were further investigated by SEM/EDS. The results indicated that the used soil amendments enhanced the binding of Zn, Pb, and Cd on Fe/Mn/Al oxides/hydroxides, which in turn resulted in the stabilisation of the target metals.
Keywords: železo; Metals, Heavy; Iron; Oxides; olovo; Soil Pollutants; látky znečišťující půdu; půda; Lead; Zinc; zinek; Cadmium; Environmental Restoration and Remediation; těžké kovy; kadmium; oxidy; regenerace a remediace životního prostředí; Soil; Charcoal; dřevěné a živočišné uhlí